Green credit policy and total factor productivity: Evidence from Chinese listed companies - Shu Guo; ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2022)
The green credit policy plays a vital role in promoting enterprise upgrading. Using a thirteen year panel data of listed companies in China (2007 2019), this study uses the difference in differences (DID) method to examine the effects of the Green Credit Guidelines in 2012 (GCG2012) on the firm level total factor productivity (TFP). Our results show that the GCG2012 significantly increases the TFP of companies in green credit restricted industries. This finding remains robust through employing the PSM-DID model, alternating the treatment group, changing the sample period, and controlling the effects of other environmental policies and financial crises. This effect is more pronounced for private enterprises, companies with worse debt paying ability, companies in highly competitive industries and companies in regions with higher financial liberalization. The impact mechanism test indicates that increasing the green innovation and reducing the agency costs (including green agency costs and traditional agency costs) are two possible channels to boost firm level TFP. Further analysis shows that the GCG2012 is effective not only for heavily polluting industries but also for light polluting industries, and that the GCG2012 can improve the economic performance of firms in green credit restricted industries. Overall, this study reveals the micro mechanisms behind the long term impact of the GCG2012 policy on firm level TFP, providing empirical evidence and policy suggestions for improving green credit policies and promoting green development.
Keywords: Q48; Q53; Q55; Q58; O13; P28; R11; H23; 330; Green credit policy; green finance; total factor productivity; PSM-DID model; China